+0  
 
0
307
2
avatar

(2x+3)(x-2)

Guest Apr 1, 2017

Best Answer 

 #1
avatar+7336 
+3

I think this is the question:

y = (2x + 3)(x - 2)

 

The y-intercept occurs when x = 0.

So, solve for y when x = 0. Plug in 0 for x and solve for y.

y = (2(0) + 3)((0) - 2)

y = (0 + 3)( 0 - 2)

y = (3)(-2)

y = -6

 

The point: (0,-6)

hectictar  Apr 1, 2017
 #1
avatar+7336 
+3
Best Answer

I think this is the question:

y = (2x + 3)(x - 2)

 

The y-intercept occurs when x = 0.

So, solve for y when x = 0. Plug in 0 for x and solve for y.

y = (2(0) + 3)((0) - 2)

y = (0 + 3)( 0 - 2)

y = (3)(-2)

y = -6

 

The point: (0,-6)

hectictar  Apr 1, 2017
 #2
avatar+91380 
+1

Remember that, at the y intercept, x will = 0......so....just substitute 0 for the x's and we have that....

 

y  = (2(0) + 3) ( 0 - 2)   = (3) (-2)   =   - 6    =  the y intercept

 

 

cool cool cool 

CPhill  Apr 1, 2017

9 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.